The mosquito microbiome includes habitat-specific but rare symbionts - Schrieke, Hans; Maignien, Loïs; Constancias, Florentin; Trigodet, Florian; Chakloute, Sarah; Rakotoarivony, Ignace; Marie, Albane; L'Ambert, Gregory; Makoundou, Patrick; Pages, Nonito; Murat Eren, A.; Weill, Mylène; et al. (Computational and structural biotechnology journal, 2022)
[Display omitted] •Oligotyping approaches reveal previously-overlooked mosquito symbionts.•Multiple closely related bacterial variants co-occur within mosquito individuals.•Rare members of the mosquito microbiota show a remarkable habitat-specificity.•Symbiont genetic diversity is more widespread than currently appreciated in insects. Microbial communities are known to influence mosquito lifestyles by modifying essential metabolic and behavioral processes that affect reproduction, development, immunity, digestion, egg survival, and the ability to transmit pathogens. Many studies have used 16S rRNA gene amplicons to characterize mosquito microbiota and investigate factors that influence host-microbiota dynamics. However, a relatively low taxonomic resolution due to clustering methods based on arbitrary threshold and the overall dominance of Wolbachia or Asaia symbionts obscured the investigation of rare members of mosquito microbiota in previous studies. Here, we used high resolution Shannon entropy-based oligotyping approach to analyze the microbiota of Culex pipiens, Culex quinquefasciatus and Aedes individuals from continental Southern France and overseas Guadeloupe as well as from laboratories with or without antibiotics treatment. Our experimental design that resulted in a series of mosquito samples with a gradient of Wolbachia density and relative abundance along with high-resolution analyses of amplicon sequences enabled the recovery of a robust signal from typically less accessible bacterial taxa. Our data confirm species-specific mosquito-bacteria associations with geography as a primary factor that influences bacterial community structure. But interestingly, they also reveal co-occurring symbiotic bacterial variants within single individuals for both Elizabethkingia and Erwinia genera, distinct and specific Asaia and Chryseobacterium in continental and overseas territories, and a putative rare Wolbachia variant. Overall, our study reveals the presence of previously overlooked microdiversity and multiple closely related symbiotic strains within mosquito individuals with a remarkable habitat-specificity.